DAILY ENGLISH SPEAKING PROFICIENT TRAINING - Rahmad Junaidi; Riyan Maulana; Nurrizqa (CV. Naskah Aceh, 2022)
This Daily Proficient English Speaking Training is a community service program which aims to provide English language learning for students. This activity was carried out by lecturers at STMIK Indonesia Banda Aceh. The activity carried out during the training was the presentation of basic English material using the Prezi presentation media. This service program is designed to train STMIK Indonesia Banda Aceh students to be able to communicate in English daily. With lecture-style training techniques and direct practice, community service activities run well, explaining the important parts of learning English and knowing how to overcome the obstacles faced when learning English.